2014
DOI: 10.1007/s11255-014-0717-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of ANCA-associated vasculitis in elderly patients

Abstract: Delivering reduced dose of immunosuppression for elderly patients was associated with satisfactory outcome and favorable treatment-related complication profile. The higher mortality in the elderly could be attributed mainly to baseline cardiovascular morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
4
12
0
2
Order By: Relevance
“…A small retrospective study, including only 52 patients over 65 years (and very few over 75 years), showed no difference in the treatment effects (including rates of leukopenia, severe infection and eGFR level) of a dose reduction with intravenous cyclophosphamide with age, and relapse rates were slightly but not significantly lower in the elderly [17]. …”
Section: Discussionmentioning
confidence: 99%
“…A small retrospective study, including only 52 patients over 65 years (and very few over 75 years), showed no difference in the treatment effects (including rates of leukopenia, severe infection and eGFR level) of a dose reduction with intravenous cyclophosphamide with age, and relapse rates were slightly but not significantly lower in the elderly [17]. …”
Section: Discussionmentioning
confidence: 99%
“…In this cohort, the morbidity and mortality were very high, with nearly 70% of patients reaching the combined end-point of ERSD or death within the first year. In another report, Haris et al [17] defined elderly patients as those aged 65 years or more and also found higher mortality in the older than in the younger patients with AAV, even though the percentage of deaths within the first year did not significantly differ (37 vs. 27%, p = 0.22).…”
Section: Prognosis Of Elderly Patients With Rpgnmentioning
confidence: 99%
“…On the other hand, elderly patients aged above 75 years were typically excluded from these trials. There is therefore relatively little data on the prognosis of elderly (and very elderly) patients with AAV [14-17]. …”
Section: Prognosis Of Elderly Patients With Rpgnmentioning
confidence: 99%
“…have usually more severe organ damage, respond less satisfactorily to treatment, are more susceptible to secondary infections, and have a poorer prognosis. [3][4][5] DAH is well known as a serious AAV symptom associated with high mortality. The guidelines suggest considering the addition of plasma exchange to corticosteroid and cyclophosphamide therapy in patients with advanced kidney dysfunction and severe DAH.…”
Section: Clinical Imagementioning
confidence: 99%